BINCANG SYARIAH IN CAFES: EVALUATING SATISFACTION AND IMPACT ON ISLAMIC LITERACY DURING RAMADHAN - Syah Awaluddin; Abubakar Kabakoran; Mar’atun Shalihah; Ahmad Lonthor; Evy Safitri Gani; Didin Bahruddin; Farid Naya (Suluh Adiluhung Publisher (SAPub), 2025)
An innovation in Islamic teaching and preaching, the